The Grid as a Healthcare Provision Tool - Hernández, V.; Blanquer, I. (Methods of Information in Medicine, 2005)
Objectives: This paper presents a survey on HealthGrid technologies, describing the current status of Grid and eHealth and analyzing them in the medium-term future. The objective is to analyze the key points, barriers and driving forces for the take-up of HealthGrids.Methods: The article considers the procedures from other Grid disciplines such as high energy physics or biomolecular engineering and discusses the differences with respect to healthcare. It analyzes the status of the basic technology, the needs of the eHealth environment and the successes of current projects in health and other relevant disciplines.Results: Information and communication technology (ICT) in healthcare is a promising area for the use of the Grid. There are many driving forces that are fostering the application of the secure, pervasive, ubiquitous and transparent access to information and computing resources that Grid technologies can provide. However, there are many barriers that must be solved. Many technical problems that arise in eHealth (standardization of data, federation of databases, content-based knowledge extraction, and management of personal data …) can be solved with Grid technologies.Conclusions: The article presents the development of successful and demonstrative applications as the key for the take-up of HealthGrids, where short-term future medical applications will surely be biocomputing-oriented, and the future of Grid technologies on medical imaging seems promising. Finally, exploitation of HealthGrid is analyzed considering the curve of the adoption of ICT solutions and the definition of business models, which are far more complex than in other e-business technologies such ASP.
Keywords: Grid; eHealth; medical information computing; medical information applications